School Environment Impact on Entrepreneurial Intention Mediated By Financial Literacy and Entrepreneurial Characteristics - Maya Syafriana Effendi; Venus F Firdaus; Nastiti Edi Utami; Jayanti Apri Emarawati; Djoni Maison; Roosdiana Roosdiana (Research Synergy Foundation, 2023)
This latest research discusses the need for a better understanding of interest in entrepreneurship in vocational high school students. Financial literacy is knowledge needed by everyone (including vocational high school students) in everyday life. It consists of studying theory, mastering practical skills and developing financial thinking, all of which will make each of us financially successful. This study aims to analyze the importance of the school environment and understanding of financial literacy and entrepreneurial characteristics that mediate students' interest in entrepreneurship. The saturated sample in this study consisted of 41 class 11 vocational student respondents, with an age range of 16-18 years who participated in community service activities held by UPI YAI lecturers. Data collection was carried out using a questionnaire survey which was carried out at the end of the presentation of the material by the lecturers with 45 question indicators. Structural Equation Model with Partial Least Square is an analytical technique used in this study. Testing path analysis with a measurement model (outer model) is carried out to find out the correctness of the answers given to the questions, namely measurements of internal consistency, convergent validity and discriminative validity, then proceed with testing the structural model (Inner Model). The results of the study show that the school environment has a direct effect on financial literacy and this financial literacy has an effect on the entrepreneurial characteristics of students. Meanwhile, the school environment and financial literacy have no effect on students' interest in entrepreneurship. This study shows that school environment, financial literacy and business characteristics can be valuable indicators to increase and trigger students' interest in entrepreneurship. These results can be used to guide policy makers where to place more emphasis on financial education for vocational